Empowering Women Entrepreneurs through Mobile Technology: A Study of Terminus Market, Jos Plateau State, Nigeria - Odekunle, Kehinde Adeleke; Musa, Apagu; Adamu, Abdulsabur Garafini; ABDULLAHI, Aminu; Oyebade, Adedoyin Oluwakayode; Oludiran, Oluwaseun Eniola; Sa'idu, Aminu; Yau, Nasiru Ahmad; Abubakar, Imran Bala (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
The rapid development of any modern society is heavily influenced by the adoption of Information and Communication Technologies (ICTs), particularly smartphones, which are crucial tools for industrial and economic growth. For women entrepreneurs, especially in developing regions, smartphones play a vital role in alleviating poverty by enhancing socio-economic opportunities. This study investigates smartphone use and satisfaction among market women, and its impacts on business communication, transactions, and decision-making among women entrepreneurs in Terminus Market, Jos, North Central Nigeria. Specifically, it explores their satisfaction with smartphone applications and services and examines how smartphones impact business communication, financial transactions, and decision-making processes. Data were gathered from 107 Terminus Market women through a structured survey. The findings indicate that most respondents were satisfied with their smartphones and viewed them as essential for business activities. Age, education level, and business type significantly influenced smartphone usage and related business outcomes. The study concludes with recommendations aimed at improving smartphone accessibility and developing business-focused applications to support market women's entrepreneurial activities further.